Kinerja Keuangan Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Ditinjau Dari Rasio Keuangan (Studi Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun2015-2018) - Budhiyanto, Arif; Swandari, Fifi; Jikrillah, Sufi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
Abstract The aim of this research is to examine and analyse the impact of activity ratio with fixed assets turnover, total assets turnover, and working capital turnover on profitability ratio with return on assets and return on equity as the measurement standart. The objects of this research were Food and Beverages Industries listed at BEI in 2015-2018 period. According to the above objectives, six hypotheses have been formulated. The samples in this research were taken by “sampling jenuh” method using certain criteria to be fulfilled. This research used 16 samples, which one of them did not fulfill the criteria, two of them have negatif financial report and three of them have not continue published financial report. To solve the problem, this research used multiple regression analysis processed by SPSS 16.0. The result of the research showed that fixed assets turnover, total assets turnover and working capital turnover had impacts on return on assets in the first equation. In the second equation fixed assets turnover and working capital turnover had impact on return on equity. Meanwhile, total asset turnover did not have impact on return on equity in second equation. Keywords: Fixed assets turnover, Total assets turnover, Working capital turnover Return on assets, Return on equity